Highly conductive and transparent coatings from flow-aligned silver nanowires with large electrical and optical anisotropy. Issue 11 (9th March 2020) - Xu, Ye; Ge, Dengteng; Calderon-Ortiz, Gabriel A.; Exarhos, Annemarie L.; Bretz, Coline; Alsayed, Ahmed; Kurz, Dave; Kikkawa, J. M.; Dreyfus, Remi; Yang, Shu; Yodh, A. G.
Abstract : A robust flow alignment technique generates conductive and transparent silver nanowire coatings with tunable alignment and anisotropy. Abstract : Conductive and transparent coatings consisting of silver nanowires (AgNWs) are promising candidates for emerging flexible electronics applications. Coatings of aligned AgNWs offer unusual electronic and optical anisotropies, with potential for use in micro-circuits, antennas, and polarization sensors. Here we explore a microfluidics setup and flow-induced alignment mechanisms to create centimeter-scale highly conductive coatings of aligned AgNWs with order parameters reaching 0.84, leading to large electrical and optical anisotropies. By varying flow rates, we establish the relationship between the shear rate and the alignment and investigate possible alignment mechanisms. The angle-dependent sheet resistance of the aligned AgNW networks exhibits an electronic transport anisotropy of ∼10× while maintaining low resistivity (<50 Ω sq −1 ) in all directions. When illuminated, the aligned AgNW coatings exhibit angle- and polarization-dependent colors, and the polarized reflection anisotropy can be as large as 25. This large optical anisotropy is due to a combination of alignment, polarization response, and angle-dependent scattering of the aligned AgNWs.